Impact of market reforms on technology adoption and profitability: The case of tomato farmers in India - Kotamraju, Nirmal Ravi Kumar; Babu, Suresh Chandra; Maligireddy, Jagan Mohan Reddy (Center for Applied Economics Research, 2021)
Market reforms affect the development of agribusiness and remain contentious in many developing countries. This study contributes to the debate and the lack of evidence on the impact of marketing reforms on the welfare of farmers. It focused on the impact of direct marketing in tomato cultivating farmers with Super Markets (SMs) on the adoption of modern production technologies and the realization of net returns in India. Primary data was collected from 500 sample farmers and applied to the Seemingly Unrelated Regression (SUR) model to analyze the impact of SMs participation on the adoption of modern production technologies and the realization of net income. The findings revealed that SMs participation decisions, interactions with SMs personnel, land holding size and lucrative prices offered by SMs are influential factors in the use of modern inputs viz., organic manures, drip irrigation, micronutrients and for the realization of higher net income from tomato cultivation. Reduced transaction costs, assured marketing, the mitigation of both production and marketing risks, enhancing the commercial outlook of farmers, etc., are the other benefits due to market linkages of tomato farmers with corporate firms.